Band edge states, intrinsic defects, and dopants in monolayer HfS2 and SnS2 - Yuzheng Guo (Applied Physics Letters, 2018)
Although monolayer HfS2 and SnS2 do not have a direct bandgap like MoS2, they have much higher carrier mobilities. Their band offsets are favorable for use with WSe2 in tunnel field effect transistors. Here, we study the effective masses, intrinsic defects, and substitutional dopants of these dichalcogenides. We find that HfS2 has surprisingly small effective masses for a compound that might appear partly ionic. The S vacancy in HfS2 is found to be a shallow donor while that in SnS2 is a deep donor. Substitutional dopants at the S site are found to be shallow. This contrasts with MoS2 where donors and acceptors are not always shallow or with black phosphorus where dopants can reconstruct into deep non-doping configurations. It is pointed out that HfS2 is more favorable than MoS2 for semiconductor processing because it has the more convenient CVD precursors developed for growing HfO2.